A method for preparing high conductive ceramic powder

By covering the ceramic powder with graphene, the problems of easy oxidation of existing ceramic powders and uneven dispersion of conductive materials are solved, and the preparation of ceramic powder with high conductivity and corrosion resistance is achieved.

CN119751022APending Publication Date: 2025-04-04LIAOYANG JINLI PHOTOELECTRIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411823583.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing ceramic powders with low resistivity and high conductivity are prone to oxidation during use, and their performance is degraded, and it is difficult to disperse evenly when adding conductive materials, resulting in reduced conductivity and reduced material strength.

Method used

By mixing metal oxide or metal carbide ceramic powder with magnesium powder, a magnesium thermal reaction is carried out under vacuum, and graphene is coated on the surface of the ceramic powder to form a graphene-covered ceramic powder.

Benefits of technology

It realizes high electrical conductivity, high thermal conductivity, high density and corrosion resistance of ceramic powder, and can be produced on a large scale, with stable performance and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751022A_ABST
    Figure CN119751022A_ABST
Patent Text Reader

Abstract

A method for preparing a highly conductive ceramic powder belongs to the technical field of functional ceramic powder preparation. It is mainly invented to solve the problems that low-resistivity and high-conductivity ceramic powders are easily oxidized, resulting in performance degradation. Magnesium powder and ceramic powder are placed in a mixer, protective gas is passed into the mixer, the mixed materials are loaded into a graphite crucible and placed in a vacuum heating furnace, and after vacuuming and exhausting the air, the temperature is raised to 640-650°C, maintained for 30-60 minutes, and carbon dioxide gas is passed into the vacuum heating furnace. After the pressure balance reaction is completed. Continue to heat up to make the temperature in the vacuum heating furnace reach 800°C-1400°C, keep warm for 1-2 hours, turn off the power, cool the vacuum heating furnace to below 80°C, and open the furnace to discharge the material. After ball milling, graphene-coated ceramic powder is obtained. The advantages are that it has the characteristics of high conductivity, high thermal conductivity, high density and high corrosion resistance of graphene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional ceramic powder preparation, and in particular relates to a method for preparing high-conductive ceramic powder. Background Art

[0002] Conductive ceramic powder is a functional material with electrical conductivity. It has the advantages of ceramics such as high temperature resistance, corrosion resistance, wear resistance, and light weight, and also has the electrical conductivity of metals. Therefore, it is widely used in electronic devices such as capacitors, oscillators, filters, sensors, conductive adhesives, etc. It is also widely used in functional coating materials such as wave absorption, corrosion resistance, antistatic, and electromagnetic shielding. In particular, low-resistivity and high-conductivity ceramic powders have important application prospects in the fields of electronics, communications, aerospace, and automobiles.

[0003] Currently, low-resistivity and high-conductivity ceramic powders on the market are mainly achieved by adding silver powder to ceramic powder. The amount of silver powder added is more than 50%, which is not only expensive, but also easily oxidized during use, resulting in performance degradation and a short service life. There are also some products that achieve high conductivity by adding conductive carbon black, graphene slurry, carbon nanotubes, etc. to ceramic powder. However, the above materials are very easy to agglomerate, and it is difficult to effectively and evenly disperse them during mass production, which greatly reduces their conductive performance and may even have negative effects such as reduced material strength.

[0004] With the continuous development of science and technology, conductive ceramic powder will have broader application prospects and development space due to its unique characteristics. Its preparation method also needs to be continuously improved and innovated to provide better support for its application in various fields. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a highly conductive ceramic powder, which can be made of a wide range of ceramic powders such as metal oxides and metal carbides, and graphene can be coated on the surface through a synthetic reaction and vacuum sintering thereof, so that the powder has excellent properties of graphene such as high conductivity, high thermal conductivity, high density, and corrosion resistance.

[0006] The object of the present invention is achieved in that:

[0007] Place magnesium powder and ceramic powder in a mixer, and pass protective gas (N2 or Ar2) into the mixer to avoid oxidation of magnesium powder during ball milling; control the mixer speed at 50-100 rpm and the mixing time for 2-4 hours.

[0008] The mixed materials are placed in a graphite crucible, and then placed in a vacuum heating furnace. After evacuating (≤0-1Pa) and exhausting the air, the temperature is raised (10-15℃ / min) to 640-650℃, maintained for 30-60 minutes, and then carbon dioxide gas is introduced into the vacuum heating furnace to obtain the following reaction:

[0009] 2Mg+(ceramic powder)+CO2↑=MgO2+C+(ceramic powder)

[0010] The ceramic powder can be metal oxide ceramic powder, metal carbide ceramic powder, mica or other ceramic powder.

[0011] The magnesium thermal reaction is an exothermic reaction, which will cause the temperature and pressure in the vacuum heating furnace to rise. As the carbon dioxide is consumed, the pressure drops, that is, after the pressure balance reaction is completed. Continue to heat up to 800℃-1400℃ in the vacuum heating furnace. After keeping warm for 1-2 hours, turn off the power, cool the vacuum heating furnace to below 80℃, and then open the furnace to discharge the material. After ball milling, the graphene-coated ceramic powder is obtained, which has the characteristics of high conductivity of graphene.

[0012] The particle size of magnesium powder is 200 mesh sieve, and the purity is ≥99.5%. The particle size of ceramic powder can be nanometer, micrometer or millimeter, and the purity is ≥99.5%. After briquetting test, the resistivity of graphene-coated ceramic powder is ≤0.3mΩ.cm.

[0013] The above-mentioned metal oxide and metal carbide ceramic powders can be MgO, Al2O3, SiO2, TiO2, ZrO, SiC, B4C, TiC, ZrC, etc., which are not listed here one by one. The particle size can be selected into nanometer, micrometer, or millimeter powder according to the later application. It can be a single type of ceramic powder or a variety of ceramic powders mixed in any proportion.

[0014] The weight ratio of magnesium powder to ceramic powder when mixed is 1:3-12.

[0015] The molar ratio of the introduced carbon dioxide gas to the magnesium powder is 1:1-3, and the carbon dioxide gas is excessive to ensure that Mg and carbon dioxide react fully.

[0016] The preferred sintering process temperature is 1000°C-1200°C, provided that elemental carbon does not chemically react with metal oxides.

[0017] Such as: SiO2+C=SiC+CO2↑

[0018] Al2O3+C=Al4C3+6CO↑

[0019] The present invention reduces carbon in carbon dioxide into elemental carbon by magnesium thermal method, and covers the surface of ceramic powders such as metal oxides or metal carbides, mica, etc., and heats to a certain temperature under vacuum conditions for heat preservation, so that the elemental carbon diffuses into the vacancy wells in the ceramic particles, forming sintering between carbon and ceramic powder particles. The elemental carbon exists in the form of a few layers (3-7 layers) of graphene. Therefore, ceramic powder particles coated with graphene are formed, which have excellent properties of graphene such as high conductivity, high thermal conductivity, high density, and corrosion resistance.

[0020] The present invention has the following beneficial effects: the present invention mixes nano-scale or micron-scale ceramic powder particles such as metal oxides, metal carbides, mica, etc. with magnesium powder in a vacuum furnace, generates a magnesium thermal reaction under certain process conditions, and then heats up for sintering to obtain graphene-coated ceramic powder, which has the advantages of high conductivity, high thermal conductivity, high density, and high corrosion resistance of graphene, can be mass-produced, has stable performance, and is low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD characterization view of the ceramic powder of Example 1 of the present invention;

[0022] Figure 2 It is a cooling curve diagram of Example 2 of the present invention. DETAILED DESCRIPTION

[0023] Place magnesium powder and ceramic powder in a mixer, and pass protective gas (N2 or Ar2) into the mixer to avoid oxidation of magnesium powder during ball milling; control the mixer speed at 50-100 rpm and the mixing time for 2-4 hours.

[0024] The mixed materials are placed in a graphite crucible, and then placed in a vacuum heating furnace. After evacuating (≤0-1Pa) and exhausting the air, the temperature is raised (10-15℃ / min) to 640-650℃, maintained for 30-60 minutes, and then carbon dioxide gas is introduced into the vacuum heating furnace to obtain the following reaction:

[0025] 2Mg+(ceramic powder)+CO2↑=MgO2+C+(ceramic powder)

[0026] The ceramic powder can be metal oxide ceramic powder, metal carbide ceramic powder, mica or other ceramic powder.

[0027] The magnesium thermal reaction is an exothermic reaction, which will cause the temperature and pressure in the vacuum heating furnace to increase. As the carbon dioxide is consumed, the pressure decreases, that is, the pressure balance reaction ends.

[0028] Continue to raise the temperature in the vacuum heating furnace to 800℃-1400℃, keep it warm for 1-2 hours, turn off the power, cool the vacuum heating furnace to below 80℃, and then open the furnace to discharge the materials. After ball milling, graphene-coated ceramic powder is obtained, which has the characteristics of high conductivity of graphene.

[0029] The particle size of magnesium powder is 200 mesh sieve, and the purity is ≥99.5%. The particle size of ceramic powder can be nanometer, micrometer or millimeter, and the purity is ≥99.5%. After briquetting test, the resistivity of graphene-coated ceramic powder is ≤0.3mΩ.cm.

[0030] The above-mentioned metal oxide and metal carbide ceramic powders can be MgO, Al2O3, SiO2, TiO2, ZrO, SiC, B4C, TiC, ZrC, etc., which are not listed here one by one. The particle size can be selected into nanometer, micrometer, or millimeter powder according to the later application. It can be a single type of ceramic powder or a variety of ceramic powders mixed in any proportion.

[0031] The weight ratio of magnesium powder to ceramic powder when mixed is 1:3-12.

[0032] The molar ratio of the introduced carbon dioxide gas to the magnesium powder is 1:1-3, and the carbon dioxide gas is excessive to ensure that Mg and carbon dioxide react fully.

[0033] The preferred sintering process temperature is 1000°C-1200°C, provided that elemental carbon does not chemically react with metal oxides.

[0034] Such as: SiO2+C=SiC+CO2↑

[0035] Al2O3+C=Al4C3+6CO↑

[0036] The present invention reduces carbon in carbon dioxide into elemental carbon by magnesium thermal method, and covers the surface of ceramic powders such as metal oxides or metal carbides, mica, etc., and heats to a certain temperature under vacuum conditions for heat preservation, so that the elemental carbon diffuses into the vacancy wells in the ceramic particles, forming sintering between carbon and ceramic powder particles. The elemental carbon exists in the form of a few layers (3-7 layers) of graphene. Therefore, ceramic powder particles coated with graphene are formed, which have excellent properties of graphene such as high conductivity, high thermal conductivity, high density, and corrosion resistance.

[0037] Embodiment 1;

[0038] The method for preparing graphene-coated magnesium oxide ceramic powder in this embodiment;

[0039] Raw materials: magnesium powder, particle size ≤300 mesh, purity ≥99.95%;

[0040] Magnesium oxide powder, particle size ≤ 1000 mesh, purity ≥ 99.5%;

[0041] Take 1kg of magnesium powder and 10kg of magnesium oxide powder, load them into the mixer, and fill the mixer with nitrogen or argon for protection. Turn the mixer at 70 rpm and mix for 3 hours. Take out the mixture and put it into the graphite crucible, then put the graphite crucible into the medium frequency induction vacuum furnace, and the vacuum pressure is ≤0.1Pa. Start the power supply to heat, the heating rate is 10-15℃ / min, rise to 640℃-650℃, keep warm for 40 minutes, and then slowly introduce CO2 gas, which is bottled and controlled by the flow rate.

[0042]

[0043] From the above formula, we can get:

[0044] (2×24)Mg:(44)CO2

[0045] Mg 1kg:CO2 0.91kg×3 (the molar ratio of magnesium powder to carbon dioxide is 1:3)

[0046] 2.7kg of CO2 needs to be introduced;

[0047] When CO2 gas is introduced, magnesium thermal reaction occurs, causing the temperature in the vacuum furnace to rise. When the temperature is balanced, the reaction ends. At this time, continue to increase the heating power of the vacuum furnace, the heating rate is 20-30 degrees / minute, the temperature is raised to 1100℃-1200℃ and kept warm for 60 minutes, then the power is turned off and the powder is cooled with the furnace. When the temperature drops below 50℃, the furnace can be opened to take out the materials. After ball milling and mixing, the finished graphene-coated ceramic powder can be obtained, and its carbon content is:

[0048] 2Mg+Mg0+C02=2Mg0+Mg0+C

[0049] 1kg+10kg+0.92kg=1.67kg+10kg+0.25kg

[0050] C = (0.25 / 11.92)% = 2.09%

[0051] in conclusion:

[0052] 1. The resistivity of the powder after briquetting is ≤0.3mΩ.cm;

[0053] 2. The powder XRO characterization results show three characteristic peaks of graphene (see Figure 1 );

[0054] 3. Powder TEM characterization of graphene-coated magnesium oxide samples, with graphene diffraction patterns and lattice fringes and wrinkle morphology photos, with 7 to 13 graphene layers;

[0055] 4. Add graphene-coated ceramic powder in a certain proportion to traditional epoxy zinc-rich primer to replace part of the zinc powder. The zinc powder content is reduced from ≥80% to ≤30%, making the product lightweight. The density is reduced from 3.2 to 3.4 kg / L to 1.6 to 1.8 kg / L. The neutral salt spray test resistance exceeds 3,000 hours, which is 3 to 5 times the original.

[0056] The product anti-corrosion mechanism is mainly manifested as:

[0057] 1. Physical shielding: Graphene coated with magnesium oxide ceramic powder has high conductivity, corrosion resistance and density, which can block and extend the path of corrosive media.

[0058] 2. Anodic protection: Graphene coated with magnesium oxide ceramic powder exists stably in the paint film, and it is not easy to form a conductive circuit with the Fe substrate, so the conductive path of zinc powder is still unobstructed, which activates the zinc powder and increases its utilization rate.

[0059] Embodiment 2;

[0060] Raw materials: magnesium powder particle size ≤300 mesh, purity ≥99.95%;

[0061] Silicon carbide powder particle size ≤ 1000 mesh, purity ≥ 99.5%;

[0062] Take 1kg magnesium powder and 5kg silicon carbide and put them into the mixer, fill with oxygen for protection, rotate at 100 rpm, mix for 4 hours, take out and put into the graphite crucible. Put the loaded crucible into the medium frequency induction vacuum furnace, evacuate (pressure ≤ 0.1Pa), start the power supply for heating, the heating rate is 10℃~15℃ / minute, rise to 640℃~650℃, keep warm for 40 minutes, and then slowly introduce CO2 gas, the amount of Mg:CO2=1:3, about 2.7kg. When CO2 gas is introduced, the magnesium thermal reaction will cause the temperature in the vacuum furnace to rise, and the reaction ends when the temperature reaches equilibrium. At this time, continue to increase the heating power of the vacuum furnace to 1100℃~1200℃, keep warm for 60 minutes and then turn off the power. The powder cools down with the furnace to below 50℃, open the furnace to take out the material, and break it up by ball milling to obtain graphene-coated silicon carbide (containing part of magnesium oxide) powder.

[0063] Its carbon content is:

[0064] 2Mg+SiC+CO2↑=2MgO+SiC+C

[0065] 1kg+5kg+0.92kg=1.67kg+5kg+0.25kg

[0066] C = (0.25 / 6.92)% = 3.61%

[0067] The resistivity of the powder after briquetting is ≤0.1mΩ.cm

[0068] Graphene-coated ceramic powder is added to epoxy resin in a certain proportion, with the weight of graphene-coated ceramic powder accounting for about 1 / 3 of the total solid weight, to prepare a coating material. The coating material is applied to the surface of a container, and another container of the same material, volume, and surface area is not coated with any coating. The same weight of transformer oil is placed in the container, and then the oil temperature is raised to 100°C. After keeping warm for 10 minutes, the heater is turned off and cooled while keeping warm. The heat dissipation effect of the coating is tested. When the temperature of the coated container drops by 60°C, the temperature of the coated container drops by 48°C, which has a significant enhanced heat dissipation effect (see Figure 2 ). Its mechanism: Graphene coated ceramic powder has the characteristics of high auxiliary emissivity, which strengthens radiation heat transfer and improves heat dissipation efficiency.

[0069] The above embodiments are provided to illustrate the technical feasibility of the present invention, and are not intended to limit the actual methods of the present invention. For those skilled in the art, other different forms of components and process variations can be made based on the above embodiments. It is not possible to cite all implementation schemes here, and all changes or modifications derived from the technical solutions of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a highly conductive ceramic powder, characterized in that: Place magnesium powder and ceramic powder in a mixer, pass protective gas into the mixer, put the mixed materials into a graphite crucible, and then place it in a vacuum heating furnace. After vacuuming and exhausting the air, heat it to 640-650℃ and keep it for 30-60 minutes, then pass carbon dioxide gas into the vacuum heating furnace to obtain the following reaction: 2Mg+(ceramic powder)+CO2↑=MgO2+C+(ceramic powder) The magnesium thermal reaction is an exothermic reaction, which will cause the temperature and pressure in the vacuum heating furnace to rise. As the carbon dioxide is consumed, the pressure drops, that is, the pressure balance reaction is completed; continue to heat up to make the temperature in the vacuum heating furnace reach 800℃-1400℃, after keeping warm for 1-2 hours, turn off the power, cool the vacuum heating furnace to below 80℃, and then open the furnace to discharge the materials; after ball milling, graphene-coated ceramic powder is obtained.

2. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: The ceramic powder is metal oxide ceramic powder, metal carbide ceramic powder, mica or other ceramic powder.

3. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: The particle size of the magnesium powder is 200 mesh sieve, and the purity is ≥99.5%. The particle size of the ceramic powder can be nanometer, micron or millimeter, and the purity is ≥99.5%.

4. The method for preparing a highly conductive ceramic powder according to claim 2, wherein: The metal oxide and metal carbide ceramic powders can be MgO, Al2O3, SiO2, TiO2, ZrO, SiC, B4C, TiC, ZrC, etc., and their particle sizes can be selected as nanometer, micron, or millimeter powders according to later applications. They can be single-variety ceramic powders or multiple ceramic powders mixed in any proportion.

5. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: The weight ratio of magnesium powder to ceramic powder when mixed is 1:3-12.

6. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: The molar ratio of the introduced carbon dioxide gas to the magnesium powder is 1:1-3, and the carbon dioxide gas is excessive to ensure that Mg and carbon dioxide react fully.

7. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: The preferred sintering process temperature is 1000°C-1200°C.

8. The method for preparing a highly conductive ceramic powder according to claim 1, wherein: Control the mixer speed at 50-100 rpm and the mixing time is 2-4 hours.